UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN AKIDAH AKHLAK DI MI MIFTAHUL HUDA KEBOLEDAN - Aulia Safitri; Taukhid Mubarok (CV. Adiba Aisha Amira, 2024)
The teaching of Moral Aqidah aims to help all students grow in morals and morals. Support their beliefs. The use of facilities and infrastructure plays a role in the success of this teaching and learning process. Learning resources, devices, media and learning strategies that are appropriate to the student's situation. If the learning topic is arranged according to the chosen learning method, appropriate selection stages are carried out. Teaching techniques make it easier to understand the content. An essential part of living together is educational ethics. Because if a student's lack of character and moral qualities is based on this, then no matter how smart and intelligent the student is, he or she will not be able to show good character in the future. The method used in this research is qualitative research. Research is a description and analysis of phenomena, events, social activities, attitudes, beliefs, perceptions and thoughts of individuals or groups of people, or research strategies that are integrated into the circumstances and events studied. This research examines teacher strategies in developing efficient methods of teaching moral beliefs, especially teacher strategies in applying interesting strategies, and building reciprocal communication between teachers and students at MI Miftahul Huda Keboledan. Creating Moral Creeds at MI Miftahul Huda Keboledan The learning process is good, effective and in accordance with educational standards.